Effects of neonatal fentanyl on late adolescent opioid-mediated behavior - Crawford, Cynthia A.; Taylor, Jordan A.; Park, Ginny I.; Rios, Jasmine W.; Bunch, Joseph; Greenwood, Constance J.; Lopez Sanchez, David Y.; Gonzales, Diego J. (Frontiers in Neuroscience, 2023)
Because of the steady increase in the use of synthetic opioids in women of child-bearing age, a large number of children are at risk of exposure to these drugs prenatally or postnatally through breast milk. While there is an older literature looking at the effects of morphine and heroin, there are relatively few studies looking at the long-term effects of high potency synthetic opioid compounds like fentanyl. Thus, in the present study, we assessed if exposure to fentanyl in male and female rat pups during a period roughly equivalent with third trimester of CNS development altered adolescent oral fentanyl self-administration and opioid mediated antinociception. We treated rats with fentanyl (0, 10 or 100 µg/kg sc) from postnatal day (PD) 4 to PD 9. The fentanyl was administered daily in two injections given 6 h apart. After the last injection on PD 9, rat pups were left alone until either PD 40 where they began fentanyl self-administration training or PD 60 where they were tested for morphine- (0, 1.25, 2.5, 5, or 10 mg/kg) or U-50,488- (0, 2.5, 5, 10 or 20 mg/kg) induced antinociception. In the self-administration study, we found that female rats had more active nose pokes than male rats when receiving a fentanyl reward but not a sucrose alone solution. Early neonatal fentanyl exposure did not significantly alter fentanyl intake or nose poke responding. In contrast, early fentanyl exposure did alter antinociception in both male and female rats. Specifically, fentanyl (10 µg/kg) pretreatment increased baseline paw-lick latencies and the higher dose of fentanyl (100 µg/kg) reduced morphine-induced paw-lick latencies. Fentanyl pretreatment did not alter U-50,488 mediated antinociception. This study illustrated that exposure to fentanyl during early development potentially has long-lasting effects on mu opioid mediated behavior. It also suggested that females may be more susceptible to fentanyl abuse than males.